Determining the Origins of Human Immunodeficiency Virus Type 1 Drug-resistant Minority Variants in People Who Are Recently Infected Using Phylogenetic Reconstruction. (11th December 2018) - Mbisa, Jean L; Kirwan, Peter; Tostevin, Anna; Ledesma, Juan; Bibby, David F; Brown, Alison; Myers, Richard; Hassan, Amin S; Murphy, Gary; Asboe, David; Pozniak, Anton; Kirk, Stuart; et al.
Abstract: Background: Drug-resistant minority variants (DRMinVs) detected in patients who recently acquired human immunodeficiency virus type 1 (HIV-1) can be transmitted, generated de novo through virus replication, or technical errors. The first form is likely to persist and result in treatment failure, while the latter two could be stochastic and transient. Methods: Ultradeep sequencing of plasma samples from 835 individuals with recent HIV-1 infection in the United Kingdom was performed to detect DRMinVs at a mutation frequency between 2% and 20%. Sequence alignments including >110 000 HIV-1 partial pol consensus sequences from the UK HIV Drug Resistance Database (UK-HDRD), linked to epidemiological and clinical data from the HIV and AIDS Reporting System, were used for transmission cluster analysis. Transmission clusters were identified using Cluster Picker with a clade support of >90% and maximum genetic distances of 4.5% or 1.5%, the latter to limit detection to likely direct transmission events. Results: Drug-resistant majority variants (DRMajVs) were detected in 66 (7.9%) and DRMinVs in 84 (10.1%) of the recently infected individuals. High levels of clustering to sequences in UK-HDRD were observed for both DRMajV (n = 48; 72.7%) and DRMinV (n = 63; 75.0%) sequences. Of these, 43 (65.2%) with DRMajVs were in a transmission cluster with sequences that harbored the same DR mutation compared to only 3 (3.6%) sequences with DRMinVs ( P < .00001, Fisher exact test). Evidence of likely direct transmission of DRMajVs was observed for 25/66 (37.9%), whereas none were observed for the DRMinVs ( P < .00001). Conclusions: Using a densely sampled HIV-infected population, we show no evidence of DRMinV transmission among recently infected individuals. Abstract : Phylogenetic reconstruction shows no evidence of drug-resistant minority variants (DRMinVs) in patients with recent human immunodeficiency virus type 1 infection resulting from a transmission event. Therefore, the majority of DRMinVs in people recently infected are most likely generated de novo.